Financial Factors and Manufacturing Exports : Firm-Level Evidence from Egypt - Kiendrebeogo, Youssouf; Minea, Alexandru (Taylor and Francis, 2017)
This paper focuses on the effects of financial factors on manufacturing firms’ export participation in a panel of Egyptian manufacturing firms over the 2003–2008 period. Our main results show that financial constraints reduce export participation of Egyptian firms, while financial liquidity improves it. Moreover, financial constraints have a negative impact on alternative measures of export activity, namely, export intensity and the time the firm takes before starting to export. Consequently, adding to the scarce literature on developing countries, our results support an important impact of financial factors on Egyptian firms’ participation in international trade.